Inter-laboratory optimization of protein extraction, separation, and fluorescent detection of endogenous rice allergens. Issue 11 (1st November 2016) - Satoh, Rie; Teshima, Reiko; Kitta, Kazumi; Lang, Gang-Hua; Schegg, Kathleen; Blumenthal, Kenneth; Hicks, Leslie; Labory-Carcenac, Bénédicte; Rouquié, David; Herman, Rod A; Herouet-Guicheney, Corinne; Ladics, Gregory S; et al.
Abstract: In rice, several allergens have been identified such as the non-specific lipid transfer protein-1, the α-amylase/trypsin-inhibitors, the α-globulin, the 33 kDa glyoxalase I (Gly I), the 52–63 kDa globulin, and the granule-bound starch synthetase. The goal of the present study was to define optimal rice extraction and detection methods that would allow a sensitive and reproducible measure of several classes of known rice allergens. In a three-laboratory ring-trial experiment, several protein extraction methods were first compared and analyzed by 1D multiplexed SDS-PAGE. In a second phase, an inter-laboratory validation of 2D-DIGE analysis was conducted in five independent laboratories, focusing on three rice allergens (52 kDa globulin, 33 kDa glyoxalase I, and 14–16 kDa α-amylase/trypsin inhibitor family members). The results of the present study indicate that a combination of 1D multiplexed SDS-PAGE and 2D-DIGE methods would be recommended to quantify the various rice allergens. Graphical abstract: : Representative multiplexed detection and 2D-DIGE profile of rice endogenous allergens.